Towards a future national vision in support of the competitive tourism advantage in Iraq - Wazni, Adil Issa Kadhim; jasim, Radhi hmood; Qasim, Nisreen Ghali (International Journal of Psychosocial Rehabilitation, 2020)
The field Competitiveness is an important for scientific research, because it plays an important role in the economies of countries, as countries strive to increase their competitiveness by increasing the level of production of goods and services in terms of quality and price, and Iraq, like any other country that seeks to do this, but an observer of Iraqi economic activity It is noted that competition will not receive this attention by decision makers, especially at the level of tourism competitiveness, because Iraq is still outside the evaluation of indicators of tourism competitiveness. And its indicators, with the proposal of a competitive advantage model for tourism to increase the competitiveness of the tourist destination in Iraq, with a summary of strategies that can be used to enhance the reality of Iraqi tourism by forming a competitive team for tourism aimed at improving the competitiveness of tourism activities, and assisting decision-makers in making relevant decisions In this field, as well as proposing a national strategic plan for the development of tourism activities. In Iraq, it competitiveness maintains for strategies.